2020
DOI: 10.1080/13676261.2020.1844172
|View full text |Cite
|
Sign up to set email alerts
|

Incapacitated sexual assault among youths: beyond the perpetrator tactics framework

Abstract: The issue of incapacitated sexual assault (ISA) among youths has received increased attention among researchers. Still our understanding of the phenomenon is so far limited. Most research to date departs from an underlying "perpetrator tactics" framework in which ISA is understood as acts of deliberate exploitation of vulnerable victims. Our analysis suggests that this framework represents an overly narrow understanding of how ISA happens among youths. Based on analyses of short written descriptions of ISA exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 32 publications
0
10
0
2
Order By: Relevance
“…A Norwegian study reported that 7% of adolescent girls who had been intoxicated with alcohol in the previous year had experienced sexual assault when incapacitated by drunkenness (Pape, 2014). Another Norwegian study, using the same measure, found a similar rate for slightly older girls, and a rate of 2% among boys (Stefansen et al, 2020a). Thus, we investigate potential links between both types of victimization and the use of alcohol and illegal substances.…”
Section: Alcohol Use Substance Use and Partyingmentioning
confidence: 92%
“…A Norwegian study reported that 7% of adolescent girls who had been intoxicated with alcohol in the previous year had experienced sexual assault when incapacitated by drunkenness (Pape, 2014). Another Norwegian study, using the same measure, found a similar rate for slightly older girls, and a rate of 2% among boys (Stefansen et al, 2020a). Thus, we investigate potential links between both types of victimization and the use of alcohol and illegal substances.…”
Section: Alcohol Use Substance Use and Partyingmentioning
confidence: 92%
“…The assaults from younger adults are similar to the latent classes of peer assault in that they involve alcohol but are distinguished from them by the assailant being a stranger. Thus, they are not likely linked to partying, which is the context for most sexual assaults among young people (Lorenz & Ullman, 2016; Stefansen et al, 2021), though this requires further exploration. The assaults by older adults share characteristics of child sexual abuse, where the assailant grooms or takes advantage of the child’s trust (Whittle et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Research on the scope of sexual violence among young people has developed in recent years. Studies have been conducted on both the general youth population (Gewirtz-Meydan & Finkelhor, 2020; Stefansen et al, 2021) and on more selected populations, such as students pursuing higher education (Fedina et al, 2018). Overall, these studies have identified sexual violence as a widespread phenomenon among young people, despite the increasing efforts in many countries to prevent it.…”
Section: Distinguishing Types Of Sexual Assault Among Young People: A...mentioning
confidence: 99%
“…Og hva karakteriserer situasjonene de skjer i? En norsk studie (Stefansen et al, 2020) har undersøkt disse spørsmålene basert på korte beskrivelser av festovergrep fra ungdom i 18-19-årsalderen som deltok i en surveystudie. Analysen peker mot at festovergrep har bakgrunn i to ganske ulike sosiale dynamikker.…”
Section: Forekomst Og Fenomenforståelserunclassified